The “Revisionist Revolution” and Future Prospects of Vygotskian Studies - Maidansky, A.D. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2021)
Abstract only This article provides critical analysis of A. Yasnitsky’s project of “Cultural-Historical Gestalt Psychology.” He uses this term to describe Vygotsky’s biggest discovery and the future of Vygotsky studies. Yasnitsky discards the activity approach to studying the human mind and reduces the social nature of personality to an “aspect” that did not receive serious elaboration in Vygotsky’s works. In the present article, it is argued that the prospect of the development of cultural-historical theory consists in elaborating on Vygotsky’s project of “height / acmeist psychology.” Its subject matter is “the reverse movement from consciousness to life,” as Vygotsky put it. The purpose of height psychology is to help humans master their affects by means of concepts. This science realizes “the motion toward freedom — toward a life guided by reason.” В статье проводится критический анализ проекта «культурно-исторической гештальтпсихологии», продвигаемого А. Ясницким. Этим термином он описывает главное открытие Выготского и будущее Vygotsky studies (исследований Выготского). Ясницкий отвергает деятельностный подход к исследованию психики и сводит социальную природу человеческой личности всего лишь к «аспекту», не получившему серьезной разработки в трудах Выготского. В этой статье доказывается, что перспектива развития культурно-исторической теории заключается в разработке проекта «вершинной/акмеистической психологии». Ее предмет — «обратное движение от сознания к жизни», по определению Выготского. Предназначение вершинной психологии состоит в том, чтобы помочь человеку овладеть своими аффектами при помощи понятий. Эта наука осуществляет «движение к свободе — к жизни по руководству разума».